Analisis Yuridis Terhadap Pelanggaran Hak Cipta Permainan Video (Video Games) Berupa Pembajakan Secara Online - Vania Irawan (JIPRO: Journal of Intellectual Property, 2020)
Video games are games that can be played by one or more people which are produced by computer programs on a television screen or other display screen. Video games are included in a protected work in accordance with Article 40 paragraph (1) letter r and Article 59 paragraph (1) letter d of Law No. 28 of 2014 on Copyright. The nature and elements of video games are complex, creating confusion regarding the video game category. In some countries, video games are included in the category of computer programming while in other countries, video games are included in the category of audiovisual. In addition, another difficulty that arises is the copyright holder of video games because as we know, the video games that are widely played these days, are created by game developers who consist of not only one or two people but hundreds of experts and professionals. Then, another problem is regarding video game online piracy. This has happened so often that it becomes one of the game developers concern and restlesness about every time they launch a new video game. So it also examines the prevention and protection of video games being pirated online.